DISCOURSE` OF SINGLE PRESIDENTIAL CANDIDATE - Hidayat; Kertabudi, Djamu; AR, Maman Suherman (International Journal of Psychosocial Rehabilitation, 2020)
Discourse of single Presidential Candidate which was blown by the great Political Party has invited prolonged discourse, thus becoming the topic of discussion in various circles While in the public spawns a variety of suspicions which think of this as a concrete form to perpetuate the power. Concrete steps being undertaken through political communication with various Leaders of Political Parties. Various consequences when political communication is successful in the achievement of mutual agreement with all or most of the political parties, so one of the consequences to the House of Representatives will return as “toothless tiger” and positioned as “stamp institution”. In the sense of loss of the role of the legislative institution in realizing “Check & Balance” in the implementation of Government.